Prevention of Recurrent Urinary Tract Infections in Postmenopausal Women - Fernando, Darrell; Santoso, Budi I (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To determine the most effective and applicable methods to reduce recurrence of urinary tract infections in postmenopausal women. Method: A search was conducted on Pubmed, NEJM, BMJ, and Google. After screening and selection, six articles were considered useful; comprising of two original research articles, one systematic review, and three society guidelines. Result: Society guidelines recommended continuous antimicrobial prophylaxis, with postcoital antimicrobial prophylaxis as an alternative. The first research article found similar results in continous antimicrobial prophylaxis group and intermittent antimicrobial prophylaxis group. The second research article found no significant difference in cranberry and trimethoprim group. The systematic review revealed vaginal estrogens are effective in preventing recurrent UTI, but the type of estrogen is less clear. Oral estrogens are not effective. Conclusion: Prevention of recurrent urinary tract infections in postmenopausal women include risk factor identification, non-antimicrobial prophylaxis with cranberry and vaginal estrogen preparations, and antimicrobial prophylaxis (continuous or intermittent). Keywords: postmenopausal, prevention, recurrent urinary tract infection.